Answer:
D
Step-by-step explanation:
![f(x)=(x-1)(x^2+2)^3\\f'(x)=(x-1)*3(x^2+2)^2*2x+(x^2+2)^3*1\\f'(x)=6x(x-1)(x^2+2)^2+(x^2+2)^3\\f'(x)=(x^2+2)^2[6x^2-6x+x^2+2]\\f'(x)=(x^2+2)^2(7x^2-6x+2)\\D](https://tex.z-dn.net/?f=f%28x%29%3D%28x-1%29%28x%5E2%2B2%29%5E3%5C%5Cf%27%28x%29%3D%28x-1%29%2A3%28x%5E2%2B2%29%5E2%2A2x%2B%28x%5E2%2B2%29%5E3%2A1%5C%5Cf%27%28x%29%3D6x%28x-1%29%28x%5E2%2B2%29%5E2%2B%28x%5E2%2B2%29%5E3%5C%5Cf%27%28x%29%3D%28x%5E2%2B2%29%5E2%5B6x%5E2-6x%2Bx%5E2%2B2%5D%5C%5Cf%27%28x%29%3D%28x%5E2%2B2%29%5E2%287x%5E2-6x%2B2%29%5C%5CD)
Answer: the correct answer is A. :-)
Step-by-step explanation:
4/9 divided by 4 is 1/9.
I didn't round by the answer would be 115.575042 miles per second.
Answer:
I think its A
Step-by-step explanation:
1 : 16
2 : 32
4 : 64
6 : 96
12 : 192
You find these by multiplying the pounds by ounces
So, 2 pounds * 16 ounces = 32 ounces.